Research Progress on the Pathological Mechanisms of Podocytes in Diabetic Nephropathy. (10th July 2020) - Zhang, Lili; Wen, Zhige; Han, Lin; Zheng, Yujiao; Wei, Yu; Wang, Xinmiao; Wang, Qing; Fang, Xinyi; Zhao, Linhua; Tong, Xiaolin
Abstract : Diabetic nephropathy (DN) is not only an important microvascular complication of diabetes but also the main cause of end-stage renal disease. Studies have shown that the occurrence and development of DN are closely related to morphological and functional changes in podocytes. A series of morphological changes after podocyte injury in DN mainly include podocyte hypertrophy, podocyte epithelial-mesenchymal transdifferentiation, podocyte detachment, and podocyte apoptosis; functional changes mainly involve podocyte autophagy. More and more studies have shown that multiple signaling pathways play important roles in the progression of podocyte injury in DN. Here, we review research progress on the pathological mechanism of morphological and functional changes in podocytes associated with DN, to provide a new target for delaying the occurrence and development of this disorder.